PENDIDIK PROFESIONAL DALAM AL-QUR’AN - Siskandar Siskandar; Suhendri Suhendri (el-Moona: Jurnal Ilmu Pendidikan Islam, 2020)
In this study aims to find the concept of professional educators in the Qur'an and analyze the law No. 14 of 2005. Research on professional educators in the Qur'an using a descriptive qualitative approach to this study resulted in: First Strengthening the concept of educators according to the law. Second In the Qur'an there are terms that refer to educators including Al-Murobbi, Al-Mua'llim, and Al-Muzakki who are in charge in educating, teaching, guiding, directing, training, assessing, and evaluating students in formal early education. In performing these duties, the teachers are responsible for the students, parents, nation and religion. In carrying ou their task, they also have the right to have salary, promotion, opportunities to improve their competence, as well as have an obligation to plan good instruction, and developing qualification and competence sustainably. The teachers who perform their duties are called professional, that is, having some expertise. In accordance with RI Law Number 14 Year 2015 about Teachers and Lecturers article 10 paragraph 1 mentions competencies including pedagogic, personality, social, and professional.